Germany's Corporate Governance Reforms : Has the System Become Flexible Enough? - Odenius, Jurgen (Washington, D.C. : International Monetary Fund, 2008)
This article reviews Germany's corporate governance system and the effectiveness of recent reforms. Since the early 1990s far-reaching reforms have complemented the traditional stakeholder system with important elements of the shareholder system. Instead of taking a view on the superiority of either system, this article raises the important question whether these reforms created sufficient flexibility for the market to optimize its corporate governance structure within well established social and legal norms. It concludes that there is scope for enhancing flexibility in three core areas, relating to (i) internal control mechanisms, especially the flexibility of board structures; (ii) self-dealing; and (iii) external control, particularly take-over activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet